Dynamic modeling and simulation of an Isobaric Adiabatic Compressed Air Energy Storage (IA-CAES) system. (June 2017) - Mazloum, Youssef; Sayah, Haytham; Nemer, Maroun
Highlights: A dynamic model of an isobaric adiabatic compressed air energy storage system is developed. The system time response depends mainly on the mechanical inertia of the compressor and the air turbine. The system is able to reach the steady state in a few minutes. The system is unable to reach the steady state in a few seconds unless it is already operating in standby mode. A standby mode with low speed regime is studied to reduce the efficiency losses. Abstract: This paper discusses the dynamic modeling of an innovative Isobaric Adiabatic Compressed Air Energy Storage (IA-CAES) system using "Dymola". The system is a solution to reduce the effect of the intermittence of the renewable energy sources and thus improve the penetration of these sources into the energy mix. It also enables restoring the balance between supply and demand for electricity and supporting the electrical grid. The proposed system is characterized by the recovery of the compression heat and the storage of air under fixed pressure in order to improve its efficiency and its energy density. The dynamic model takes into account the mechanical inertia of the turbo-machinery as well as the thermal inertia of the heat exchangers and the storage tanks. This allows the model to evaluate the response time of the storage system and its ability to meet the power demand. Then, it allows studying the flexibility of the storage system by evaluating the durations of the transient states and the proposals to reduce these durations. The system efficiency is 53.6%. The results show that the time required to reach the steady state is about 120 s during storage periods and 382 s during production periods. In addition, the power consumed or produced by the storage system matches with the set point with maximum delay of 6 s and maximum relative error of 9%. The system is then able to reach the nominal power in few minutes (secondary reserve). Finally, a standby mode with minimal energy consumption is studied in order to reduce the durations of the transient states and then to be able to meet the primary reserve (by reaching 33% of the nominal power in 10 s). It consists in operating the compressor at 54% and the turbine at 72% of their nominal speeds.